Exploring the Artemisia Genus: An Insight into the Phytochemical and Multi-Biological Potential of A. campestris subsp. lednicensis (Spreng.) Greuter & Raab-Straube - Adriana Trifan; Monika E. Czerwińska; Constantin Mardari; Gokhan Zengin; Kouadio Ibrahime Sinan; Izabela Korona-Glowniak; Krystyna Skalicka-Woźniak; Simon Vlad Luca (Plants, 2022)
The Artemisia L. genus includes over five hundred species with great economic and medicinal properties. Our study aimed to provide a comprehensive metabolite and bioactivity profile of Artemisia campestris subsp. lednicensis (Spreng.) Greuter & Raab-Straube collected from north-eastern Romania. Liquid chromatography with tandem high-resolution mass spectrometry (LC-HRMS/MS) analysis of different polarity extracts obtained from the aerial parts led to the identification of twelve flavonoids, three phenolic acids, two sesquiterpene lactones, two fatty acids, one coumarin, and one lignan. The antioxidant and enzyme inhibitory properties were shown in the DPPH (0.71–213.68 mg TE/g) and ABTS (20.57–356.35 mg TE/g) radical scavenging, CUPRAC (38.56–311.21 mg TE/g), FRAP (121.68–202.34 mg TE/g), chelating (12.88–22.25 mg EDTAE/g), phosphomolybdenum (0.92–2.11 mmol TE/g), anti-acetylcholinesterase (0.15–3.64 mg GALAE/g), anti-butyrylcholinesterase (0–3.18 mg GALAE/g), anti-amylase (0.05–0.38 mmol ACAE/g), anti-glucosidase (0.43–2.21 mmol ACAE/g), and anti-tyrosinase (18.62–48.60 mg KAE/g) assays. At 100 μg/mL, Artemisia extracts downregulated the secretion of tumor necrosis factor (TNF)-α in a lipopolysaccharide (LPS)-stimulated human neutrophil model (29.05–53.08% of LPS+ control). Finally, the Artemisia samples showed moderate to weak activity (minimum inhibitory concentration (MIC) > 625 mg/L) against the seventeen tested microbial strains (bacteria, yeasts, and dermatophytes). Overall, our study shows that A. campestris subsp. lednicensis is a promising source of bioactives with putative use as food, pharmaceutical and cosmetic ingredients.